2012
DOI: 10.15376/biores.7.3.2799-2808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steaming on the colour change of softwoods

Abstract: The heat treatment of softwood (i.e. spruce, pine, fir, and larch) may result in significant colour changes. During this study Scots pine and spruce samples were steamed and analysed for their altered hue and lightness. Treatments included: 0 to 22 days of steaming time at a temperature range of 70 to 100°C. The outcome included a variety of colours between the initial hues and brownish tint. These new colours are similar to that of aged furniture and indoor wooden structures. Consequently, properly steamed so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Moura and Brito 22 reported that the a * value of Eucalyptus grandis wood decreased after heat treatment, which could be related to the volatilization of certain chemical compounds, such as phenolic extractives. Tolvaj et al 23 found that the woods of Pinus sylvestris and Picea abies became darker after steam treatment, and the color hue of both species turned brown. The observed color change in both species could be attributed to the alteration of the conjugated double bond systems found mainly in extractives.…”
Section: Resultsmentioning
confidence: 99%
“…Moura and Brito 22 reported that the a * value of Eucalyptus grandis wood decreased after heat treatment, which could be related to the volatilization of certain chemical compounds, such as phenolic extractives. Tolvaj et al 23 found that the woods of Pinus sylvestris and Picea abies became darker after steam treatment, and the color hue of both species turned brown. The observed color change in both species could be attributed to the alteration of the conjugated double bond systems found mainly in extractives.…”
Section: Resultsmentioning
confidence: 99%
“…This is the process that can ensure positive effects such as uniformization of color, reduction of wood deformations, increase in wood stability in the drying process, and reduction of errors on glued panels [ 4 , 5 , 6 , 7 , 8 , 9 ]. Color changes are related to specific chemical properties of different intensities and complexity, which can affect the main chemical components and secondary components of wood in relation to the actual treatment conditions (temperature, time, and treatment environment) [ 10 , 11 , 12 , 13 ]. The steaming process partly reduces the internal growth stresses of the wood, which decreases the potential for cracking and deformations during the drying process [ 4 ].…”
Section: Introductionmentioning
confidence: 99%